Allogenic Vγ9Vδ2 T cell as new potential immunotherapy drug for solid tumor: a case study for cholangiocarcinoma. Issue 1 (8th February 2019) - Alnaggar, Mohammed; Xu, Yan; Li, Jingxia; He, Junyi; Chen, Jibing; Li, Man; Wu, Qingling; Lin, Li; Liang, Yingqing; Wang, Xiaohua; Li, Jiawei; Hu, Yi; et al.
Abstract : Background: Cholangiocarcinoma (CCA) is a highly aggressive and fatal tumor. CCA occurs in the epithelial cells of bile ducts. Due to increasing incidences, CCA accounts for 3% of all gastrointestinal malignancies. In addition to comprehensive treatments for cancer, such as surgery, chemotherapy, and radiotherapy, during the past few years, cellular immunotherapy has played an increasingly important role. As a result of our research, we have discovered the γδ T cell-based immunotherapy for CCA. Case presentation: A 30-year-old male (https://www.clinicaltrials.gov/ ID: NCT02425735 ) was diagnosed with recurrent mediastinal lymph node metastasis after liver transplantation because of Cholangiocarcinoma (stage IV). In the course of his therapy sessions, he only received allogenic γδ T cell immunotherapy from August, 2017 through February, 2018 (8 infusions in total). γδ T cells were expanded from peripheral blood mononuclear cells (PBMCs) of healthy donor, and ~ 4 × 10 8 cells were adoptive transferred to the patient. Conclusion: In the above case report of the Cholangiocarcinoma (stage IV) patient who had received liver transplantation and afterward was diagnosed with recurrent mediastinal lymph node metastasis, we clinically proved that allogenic γδ T cell treatment had no adverse effects. We observed that allogenic γδ T cell treatments positively regulated peripheral immune functions of the patient, depleted tumor activity, improved quality of life, and prolonged his life span. After 8 γδ T cell treatments, the size of lymph nodes was remarkably reduced with activity depletion. This clinical work suggested that allogenic γδ T cell immunotherapy could be developed into a promising therapy drug for CCA.